RADT-13. EARLY CONCURRENT IMMUNOTHERAPY WITH STEREOTACTIC RADIOSURGERY IS ASSOCIATED WITH PROLONGED SURVIVAL AND DECREASED DISTANT BRAIN FAILURE IN PATIENTS WITH NEWLY DIAGNOSED MELANOMA BRAIN METASTASES (MBM). (9th November 2020) - Augustyn, Alexander; Patel, Roshal; Ludmir, Ethan; Haydu, Lauren; Guha-Thakurta, Nandita; Bishop, Andrew; Chung, Caroline; Ghia, Amol; McAleer, Mary Frances; McGovern, Susan; Wang, Chenyang; Woodhouse, Kristina; et al.
Abstract: INTRODUCTION: We evaluated outcomes of patients with newly diagnosed MBM treated with concurrent immune checkpoint inhibition (ICI) and stereotactic radiosurgery (SRS) (concurrentTx), defined as treatment delivery within 30 days of each other. METHODS: Screening of 2, 617 melanoma patients who received ICI (anti-CTLA4/anti-PD1/both) between 2011-2019 identified 151 pts who received concurrentTx for MBM. Among these, 51 had newly-diagnosed MBM and received no prior ICI or SRS, and were included in the current study. Overall survival (OS) and distant brain failure (DBF) were estimated using the Kaplan-Meier method. Incidence of radiation necrosis (RN) was captured. RESULTS: Median follow up from treatment initiation (either ICI or SRS, whichever occurred first) was 37 months. Median OS was 30 months. Median interval between ICI/SRS was 12 days (range: 1-29). Twenty-two patients received ICI first and 29 received SRS first, without differences in OS (p=0.22), DBF (p=0.91), or development of RN (p=0.86). However, the interval between ICI and SRS was significant. Patients who received concurrentTx 1-11 days apart (n=25, "early") experienced a significant improvement in OS and DBF compared to 12-29 days apart (n=26, "delayed") (p=0.01, HR 2.8; 95%CI 1.3-6.2 for OS and p=0.02, HR 2.5; 95%CI 1.2-5.6 for DBF). OS and DBF at 36 months were 67% vs. 26% and 60% vs. 27%, respectively, for the early vs. delayed groups. Time to concurrentTx as a continuous variable was significantly associated with DBF (p=0.02), but not OS (p=0.06). Although not significant, more patients developed RN in the early (26.0%) versus delayed (3.8%) group (p=0.07). No additional patient or treatment differences were identified. CONCLUSIONS: Early concurrentTx was associated with prolonged OS and improved DBF in newly diagnosed MBM patients who did not receive prior CNS-directed therapy. This finding suggests therapeutic synergism related to combined early treatment and should be validated in a prospective clinical trial.